Dual-phase FDG PET/CT for predicting prognosis in operable breast cancer. (October 2022) - Ikejiri, Haruka; Sasada, Shinsuke; Emi, Akiko; Masumoto, Norio; Kadoya, Takayuki; Okada, Morihito
Abstract: Purpose: We aimed to investigate the role of dual-phase FDG PET/CT in predicting the prognosis of patients with operable breast cancer. Methods: We retrospectively reviewed the data of 998 patients who underwent radical treatment for breast cancer. Before treatment, PET/CT scans were performed 1 and 2 h after FDG administration. The maximum standardized uptake value (SUVmax) at both time points (SUVmax1 and SUVmax2) in the primary tumor and the retention index (RI) were calculated. PET recurrence risk (PET-RR) was determined based on the SUVmax1 and RI, and disease-free survival (DFS) and overall survival (OS) were evaluated according to the metabolic parameters. Propensity score matching was performed to adjust for biological characteristics. Results: The cut-off values for SUVmax1 and RI were 3 and 5%, respectively. The 5-year DFS was 94.9% and 86.1% ( P  < 0.001), and the 5-year OS was 97.6% and 92.7% ( P  < 0.001) in the low and high PET-RR groups, respectively. In multivariate analysis, high T status, nodal metastasis, the triple-negative subtype, and high PET-RR were independent factors of poor DFS. Propensity score matching revealed similar findings (5-year DFS 91.8% vs. 88.6%, P  = 0.041 and 5-year OS 97.1% vs. 94.2%, P  = 0.240, respectively). Conclusion: The combined parameters of SUVmax1 and RI on dual-phase FDG PET/CT were useful for predicting prognosis of patients with breast cancer. Patients with a high SUVmax1 and a negative time course of FDG uptake had a favorable prognosis. Highlights: SUVmax and retention index on FDG PET/CT are related with breast cancer prognosis. Breast cancer with high SUVmax but no increase over time has a favorable prognosis. Dual-phase FDG PET/CT is useful to predict the prognosis in operable breast cancer.